Asalibu Muassasah Az-Zakah fi Rofahiyah Al-Mujtama’ wa Atsariha fiHayatihim Al-Iqtishodiyyah - Muhammad Taufiq Zamzamy (Islamic Economics Journal, 2015)
Zakat is the social financing pillar of Islam. God has obliged it to the believers in His book that was revealed to the Prophet Muhammad Saw. Zakat should be distributed to people who deserve zakat funds, be regulated and managed properly. The management of the Fund in Indonesia is governed by the zakat laws No. 38 in 1999, the Act regulates the methods of management of the Fund to charity at the national level or in the local area, although the fact that the role of this legislation has not been effective for improving the welfare of the mustahiq (a person who is entitled to receive zakat). This research aims to examine one of the Amil zakat which in Indonesia, namely Amil Zakat Board of Semarang. This field study will analyze the management of zakat in Amil Zakat Board of Semarang which consists of collection and distribution of Zakat. In addition, the research will identify the problems faced by Badan Amil Zakat Semarang and looking for a solution to handling the problem for the purpose of community prosperity. The result shows that zakat collected by Badan Amil Zakat Semarang is distributed to eight asynaf  especially the dhu'afa'. Fund Management in Amil Zakat Board of Semarang is handled well. This can be evidenced by the implementation of the activities of collecting, and distributing zakaat. For getting the goal, Amil Zakat Board of Semarang develops ways and programs for the welfare of society and also to solve the problem.